2011
DOI: 10.1042/bj20111286
|View full text |Cite
|
Sign up to set email alerts
|

Retinaldehyde is a substrate for human aldo–keto reductases of the 1C subfamily

Abstract: Human AKR (aldo-keto reductase) 1C proteins (AKR1C1-AKR1C4) exhibit relevant activity with steroids, regulating hormone signalling at the pre-receptor level. In the present study, investigate the activity of the four human AKR1C enzymes with retinol and retinaldehyde. All of the enzymes except AKR1C2 showed retinaldehyde reductase activity with low Km values (~1 μM). The kcat values were also low (0.18-0.6 min-1), except for AKR1C3 reduction of 9-cis-retinaldehyde whose kcat was remarkably higher (13 min-1). S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
37
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(37 citation statements)
references
References 48 publications
(87 reference statements)
0
37
0
Order By: Relevance
“…The procedure was based on the QuikChange SiteDirected Mutagenesis Kit method (Stratagene, Leicester, UK). The mutagenic strands were sequence verified and then transformed into Escherichia coli BL21 cells, in which recombinant ALDH1A3 was expressed at 24 1C and purified, as previously described 10 and as follows: cells were lysed by sonication and the homogenate was applied onto a nickel-charged chelating Sepharose Fast Flow (GE Healthcare, Little Chalfont, UK) column (5 ml). After washing with 60 mM imidazole in 20 mM Tris-HCl, 0.5 M NaCl, pH 8.0, the enzyme was eluted with 250 mM imidazole in the same buffer.…”
Section: Molecular Analysesmentioning
confidence: 99%
“…The procedure was based on the QuikChange SiteDirected Mutagenesis Kit method (Stratagene, Leicester, UK). The mutagenic strands were sequence verified and then transformed into Escherichia coli BL21 cells, in which recombinant ALDH1A3 was expressed at 24 1C and purified, as previously described 10 and as follows: cells were lysed by sonication and the homogenate was applied onto a nickel-charged chelating Sepharose Fast Flow (GE Healthcare, Little Chalfont, UK) column (5 ml). After washing with 60 mM imidazole in 20 mM Tris-HCl, 0.5 M NaCl, pH 8.0, the enzyme was eluted with 250 mM imidazole in the same buffer.…”
Section: Molecular Analysesmentioning
confidence: 99%
“…Finally, DHRS3 may not be the only enzyme in the liver to catalyze the reduction of retinal to retinol. There may be others, including AKR1B or AKR1C, as well as other retinol dehydrogenases/reductases (29,35,36). Among AKR1B subfamily enzymes, we found that only the AKR1B7 gene is induced by RA in the liver of vitamin A-deficient, but not vitamin A-sufficient, diet-fed rats.…”
Section: Discussionmentioning
confidence: 62%
“…The conversion of retinal to retinol has been reported to be mediated through several retinol dehydrogenases (29,35,36), of which the well-conserved microsomal protein DHRS3, a member of the classical short-chain dehydrogenase reductase (SDR) superfamily, has been previously identified (15). Although DHRS3 was originally cloned from the retina, it is expressed in several non-ocular human tissues, including the liver, pancreas, heart, kidney, and lung (3,15).…”
mentioning
confidence: 99%
“…Furthermore, the enzyme was active with compounds related to the androgen receptor (AR), estrogen receptor a (ERa), mineralocorticoid receptor (MR), peroxisome proliferator-activated receptor c (PPARc), RAR and RXR (Table 4). Recently, we studied cell proliferation in human promyelocytic leukemia HL-60 cells, which endogenously express AKR1C3, and showed that the pro-proliferative action of AKR1C3 was mediated in part by the RA signaling pathway [51]. The inhibition of AKR1C3 could cause an increased flow in the 9-cis-RA synthesis and, consequently, a lower cell proliferation rate.…”
Section: Control Of Hormonal Signaling At Pre-receptor Levelmentioning
confidence: 99%
“…We have previously demonstrated that AKR1B1, 1B10, 1C1, 1C3 and 1C4 are active retinaldehyde reductases which can decrease both retinaldehyde and RA levels in cellular models [44,51], and therefore they may exert pre-receptor regulation of the RAR and RXR nuclear receptors. Additionally, members of the human AKR1A, 1B, and 1D subfamilies are able to act on lipophilic molecules other than retinoids, including steroids, prostaglandins, and polycyclic aromatic hydrocarbons [52].…”
Section: Control Of Hormonal Signaling At Pre-receptor Levelmentioning
confidence: 99%